The Effectiveness Of Moringa Leaf Extract (Moringa oleifera) on Cadmium and LDL Cholesterol Levels in Blood as Indicators of Atherosclerosis in Cadmium (Cd) Induced White Rats (Rattus norvegicus) - Vernanda Arsya Nabilla; Indah Lestari; Christ Kartika Rahayuningsih; Juliana Christyaningsih (Jurusan Teknik Elektromedik, POLTEKKES KEMENKES Surabaya, Indonesia, 2022)
Moringa leaves (Moringa oleifera) have chelating agent properties that act as natural antioxidants in binding heavy metals and free radical scavengers, with cadmium being one of the heavy metals free radicals having toxic effects on the body. Exposure to cadmium can reduce the activity of lipoprotein lipase enzymes (LPL) which function in the triglycerides and free fatty acids catabolism process, and can increase cholesterol and triglyceride levels in the blood. This study aims to determine the effectiveness of Moringa (Moringa oleifera) on Cadmium chloride-induced white rats (Rattus norvegicus) using an experimental research design with a quantitative analysis technique. This study uses the level of cadmium and LDL cholesterol for the dependent variable and the dose of Moringa leaf extract (Moringa oleifera) for its independent variable. The samples used are white rats (Rattus norvegicus) aged 8-12 weeks with a weight of 150-200 grams, along with blood drawn from the heart for the specimen. The researcher conducted the study at the Faculty of Veterinary Medicine, Airlangga University; Surabaya Health Laboratory Center; and Surabaya Bakti Analysis Laboratory from October 2021 to June 2022 using Atomic Absorption Spectrophotometry (AAS) and Chemical Analyzer BS-200. The results show that the average value of cadmium and LDL cholesterol levels in white rats in treatment group 1 are 0.605 g/dL and 8.25 mg/dL, group 2 are 0.075 g/dL & 18.5 mg/dL; and group 3 are 0.08125 g/dL and 12 mg/dL. Based on the statistical analysis of the One-Way ANOVA test, the sig. p-value is > 0.05. Thus, the average value of cadmium and LDL cholesterol has no significant difference. Compared to the 400 mg/kgBW and 500 mg/kgBW, the 600 mg/kgBW dose has the best effectiveness in reducing LDL cholesterol in white rats (Rattus norvegicus) after being induced with cadmium chloride. This study recommends consuming fresh Moringa leaves (Moringa oleifera) as much as 66.522 grams per human/day as an additional antioxidant and chelating agent.